Sequence dependent electrophoretic mobilities and melting temperatures for A-T containing oligodeoxyribonucleotides. - Wilson, W D (1987)
The electrophoretic mobilities and thermal melting properties of self complementary A-T containing dodecamer oligodeoxyribonucleotides have been investigated as a function of solution conditions. The oligomers contained tracts of nonalternating A-T base pairs of 2 (d(A2T2)3), 3 (d(A3T3)2), and 6 (d(A6T6] as well as the fully alternating (d(A-T)6) sequence. The melting temperature increased with the length of the nonalternating sequence and was approximately 12 degrees C higher in the d(A6T6) sequence than in the alternating oligomer. Under denaturing conditions all oligomers had the same electrophoretic mobility on acrylamide gels. Under conditions which favor duplex formation, the oligomers exhibited significant sequence dependent mobility differences. The mobilities of two oligomers, d(A-T)6 and d(A6-T6), were approximately equal and were less than those of the other oligonucleotides. The greatest mobility was observed for d(A2T2)3. These results are best explained by a model which requires bending at a junction of two or more continuous A or T bases with another sequence.